We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
571
1
avatar

I need understanding and help solving

 Jun 29, 2018

Best Answer 

 #1
avatar+8579 
+2

\(\sin(x +\frac{11\pi}{6})\,-\,\sin(x -\frac{11\pi}{6})\,=\,1\)

 

We can use the sum of angles formula for sine:

 

\(\sin(\alpha \pm\beta)=\sin\alpha\cos\beta\pm\cos\alpha\sin\beta\\~\\ \ \\ {\color{BlueViolet} \sin(x +\frac{11\pi}{6})=\sin x\cos\frac{11\pi}{6}+\cos x\sin\frac{11\pi}{6}\quad=(\sin x)(\frac{\sqrt3}{2})+(\cos x)(-\frac12)}\\~\\ {\color{Fuchsia} \sin(x -\frac{11\pi}{6})=\sin x\cos\frac{11\pi}{6}-\cos x\sin\frac{11\pi}{6}\quad=(\sin x)(\frac{\sqrt3}{2})-(\cos x)(-\frac12)}\)

 

 

So if...

 

\({\color{BlueViolet}\sin(x +\frac{11\pi}{6})}\,-\,{\color{Fuchsia}\sin(x -\frac{11\pi}{6})}\,=\,1\\~\\ [\,{\color{BlueViolet}(\sin x)(\frac{\sqrt3}{2})+(\cos x)(-\frac12)}\,]\,-\,[\,{\color{Fuchsia}(\sin x)(\frac{\sqrt3}{2})-(\cos x)(-\frac12)}\,]\,=\,1\\~\\ (\sin x)(\frac{\sqrt3}{2})+(\cos x)(-\frac12)-(\sin x)(\frac{\sqrt3}{2})+(\cos x)(-\frac12)\,=\,1\\~\\ 2(\cos x)(-\frac12)\,=\,1\\~\\ - \cos x\,=\,1\\~\\ \cos x\,=\,-1\\~\\ x\,=\,\pi+2\pi n\quad \text{, where }\ n\ \text{ is an integer.}\)      then...

 Jun 29, 2018
 #1
avatar+8579 
+2
Best Answer

\(\sin(x +\frac{11\pi}{6})\,-\,\sin(x -\frac{11\pi}{6})\,=\,1\)

 

We can use the sum of angles formula for sine:

 

\(\sin(\alpha \pm\beta)=\sin\alpha\cos\beta\pm\cos\alpha\sin\beta\\~\\ \ \\ {\color{BlueViolet} \sin(x +\frac{11\pi}{6})=\sin x\cos\frac{11\pi}{6}+\cos x\sin\frac{11\pi}{6}\quad=(\sin x)(\frac{\sqrt3}{2})+(\cos x)(-\frac12)}\\~\\ {\color{Fuchsia} \sin(x -\frac{11\pi}{6})=\sin x\cos\frac{11\pi}{6}-\cos x\sin\frac{11\pi}{6}\quad=(\sin x)(\frac{\sqrt3}{2})-(\cos x)(-\frac12)}\)

 

 

So if...

 

\({\color{BlueViolet}\sin(x +\frac{11\pi}{6})}\,-\,{\color{Fuchsia}\sin(x -\frac{11\pi}{6})}\,=\,1\\~\\ [\,{\color{BlueViolet}(\sin x)(\frac{\sqrt3}{2})+(\cos x)(-\frac12)}\,]\,-\,[\,{\color{Fuchsia}(\sin x)(\frac{\sqrt3}{2})-(\cos x)(-\frac12)}\,]\,=\,1\\~\\ (\sin x)(\frac{\sqrt3}{2})+(\cos x)(-\frac12)-(\sin x)(\frac{\sqrt3}{2})+(\cos x)(-\frac12)\,=\,1\\~\\ 2(\cos x)(-\frac12)\,=\,1\\~\\ - \cos x\,=\,1\\~\\ \cos x\,=\,-1\\~\\ x\,=\,\pi+2\pi n\quad \text{, where }\ n\ \text{ is an integer.}\)      then...

hectictar Jun 29, 2018

9 Online Users